2015
DOI: 10.1002/hipo.22413
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal hippocampus infusions of CNQX into the dentate gyrus disrupt expression of trace fear conditioning

Abstract: The hippocampus is essential for the consolidation of some explicit long-term memories, including trace conditioning. Lesions and pharmacological manipulations of the dorsal hippocampus (DH) have provided strong evidence for its involvement in the acquisition and expression of trace fear memories. However, no studies have specifically targeted DH subregions [CA1 and dentate gyrus (DG)] to determine their involvement in trace fear conditioning. In the present study, rats received bilateral cannulation targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 61 publications
(87 reference statements)
1
25
0
Order By: Relevance
“…However, use of the terms fear learning, fear conditioning, fear-motivated learning, fear memory, and fear extinction has become so widespread that many readers interested in these subjects might well skip altogether an article whose title does not contain those words. So they will be used here as they are in most other recent accounts of the subject (95,98,115,116,182,294,296,299,378,403,421,462,463,468,475,501,524,653).…”
Section: B Fear-motivated Learningmentioning
confidence: 99%
“…However, use of the terms fear learning, fear conditioning, fear-motivated learning, fear memory, and fear extinction has become so widespread that many readers interested in these subjects might well skip altogether an article whose title does not contain those words. So they will be used here as they are in most other recent accounts of the subject (95,98,115,116,182,294,296,299,378,403,421,462,463,468,475,501,524,653).…”
Section: B Fear-motivated Learningmentioning
confidence: 99%
“…Trace fear conditioning is similar to delay fear conditioning, except that there is a stimulus-free interval separating the conditioned stimulus (CS) and the unconditioned stimulus (US) presented. Trace fear conditioning depends upon an intact hippocampus (Pierson et al 2015).…”
Section: Impaired Hippocampal-dependent Behavior In Eef2k-ko Micementioning
confidence: 99%
“…However, one possibility is that the effects of hippocampal pharamcological manipulations on trace conditioning are highly dependent on target region. Indeed, one study found that blockade of DH AMPA receptors within the dentate gyrus, but not CA1, disrupted trace fear retrieval (Pierson, Pullins, & Quinn, 2015). Therefore, to better understand the role of the hippocampus in trace conditioning, close attention will not only need to be paid to dorsal/ventral regional differences, but also to spatially relevant inputs to the trisinaptic circuit.…”
Section: Declarative Memory and Trace Conditioningmentioning
confidence: 99%